2023
DOI: 10.1021/acs.jpclett.2c03491
|View full text |Cite
|
Sign up to set email alerts
|

Collective Variables for Conformational Polymorphism in Molecular Crystals

Abstract: Controlling polymorphism in molecular crystals is crucial in the pharmaceutical, dye, and pesticide industries. However, its theoretical description is extremely challenging, due to the associated long time scales (>1 μs). We present an efficient procedure for identifying collective variables that promote transitions between conformational polymorphs in molecular dynamics simulations. It involves applying a simple dimensionality reduction algorithm to data from short (∼ps) simulations of the isolated conformer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…Therefore, a smaller free energy barrier was observed in the Markovian milestoning process than that in the PMF, and as mentioned by Ovchinnikov, 92 Santiso, 23 and He et al , 53 the former was a more accurate representation of the free energy involved in the homogeneous nucleation process. Recently, Elishav et al 96 identified two effective collective variables, the linear combinations of the improper angles between the nitro group and the central molecular cage, by performing a harmonic linear discriminant analysis (HLDA) and MC-HLDA 104,105 on a set of labeled molecular descriptors from well-tempered Metadynamics 106 simulations, and constructed the free energy surface of the conformational polymorphism between β-CL-20 and ε-CL-20. 96 They found that the difference in free energy between β-CL-20 and ε-CL-20 was 4.0 kcal mol −1 , close to our results in this work (∼6.0 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a smaller free energy barrier was observed in the Markovian milestoning process than that in the PMF, and as mentioned by Ovchinnikov, 92 Santiso, 23 and He et al , 53 the former was a more accurate representation of the free energy involved in the homogeneous nucleation process. Recently, Elishav et al 96 identified two effective collective variables, the linear combinations of the improper angles between the nitro group and the central molecular cage, by performing a harmonic linear discriminant analysis (HLDA) and MC-HLDA 104,105 on a set of labeled molecular descriptors from well-tempered Metadynamics 106 simulations, and constructed the free energy surface of the conformational polymorphism between β-CL-20 and ε-CL-20. 96 They found that the difference in free energy between β-CL-20 and ε-CL-20 was 4.0 kcal mol −1 , close to our results in this work (∼6.0 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Today, in addition to the path-based FTS, many rare event methods have been established to perform the calculations of polymorphic transformation, such as metadynamics, adiabatic free energy dynamics, etc. 96,[107][108][109][110][111][112][113][114][115][116] This will further reveal the essence of polymorphic transformation from various aspects. (1) By using the general average-based sampling, the simulation of the replica in one sampling space covers the adjacent regions along the transition path, and connecting the adjacent points forms an unsmoothed initial string.…”
Section: Free Energy From Markovian Milestoning With Voronoi Tessella...mentioning
confidence: 95%
See 1 more Smart Citation
“…The phenomenon of polymorphism (Bernstein, 2020;Cruz-Cabeza & Bernstein, 2014;Nangia, 2008;Elishav et al, 2023) is extremely relevant for the development of science and the pharmaceutical industry. On the one hand, the presence of various crystal structures of the same compound allows one to study trends between the crystal structures and their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In two-step processes, a two-dimensional CV space representing the extent of the largest cluster and of the largest ordered domain in the nucleating phase have also emerged as good descriptors of the reaction coordinate [43,46,89,90], which also lend themselves to a theoretical description of two-step nucleation [45]. More recently, the application of Machine Learning methods and the data-driven identification of low-dimensional reaction coordinates for nucleation has emerged as a viable strategy to identify combinations of CVs that enable an effective, low-dimensional description of nucleation processes [43,148,180,181,182], that allows for the application of biased enhanced sampling by driving the polymorph-specific crystal nucleation. [167] The definition of effective CVs for describing and enhancing the sampling of complex nucleation processes in solution also hinges on our ability to define order parameters that can resolve well the atomic environments that are characteristic of specific crystalline structures.…”
Section: Collective Variablesmentioning
confidence: 99%